Public Finance and Public Policy - Gruber, Jonathan (New York Worth Publishers, 2007)
Gruber's Public Finance and Public Policy is written from the ground up to reflect current realities of public finance, enhancing its survey of traditional topics with an emphasis on empirical work and coverage of transfer programs and social insurance. The new edition is fully updated with the most recent data and research possible.
Include Index, Glossary and References
Keywords: Finance, Public -- Public welfare--Finance -- Taxation